1996
DOI: 10.1111/j.1574-6968.1996.tb08407.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the inhibitory action onSaccharomyces cerevisiaeof weak-acid preservatives, uncouplers, and medium-chain fatty acids

Abstract: This study was initiated to establish whether inhibition of growth of yeasts by medium-chain fatty acids resembled that caused by weak-acid preservatives or uncouplers. Unlike sorbic acid and 2,4-dinitrophenol, decanoic acid caused rapid cell death at its inhibitory concentration. This suggested a mode of action by medium-chain fatty acids, distinct from both weak-acid preservatives and uncouplers. Sorbic acid and 2,4-dinitrophenol both increased lag and doubling times, reduced cell yields and inhibitory conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Indeed, we show that these two enzymes are involved in the esterification of MCFAs, which are toxic compounds for yeast (24). Hence Eht1 and Eeb1 could thus be involved in their detoxification by esterification.…”
Section: S Cerevisiae May Contain Additional Medium-chain Fatty Acidmentioning
confidence: 72%
“…Indeed, we show that these two enzymes are involved in the esterification of MCFAs, which are toxic compounds for yeast (24). Hence Eht1 and Eeb1 could thus be involved in their detoxification by esterification.…”
Section: S Cerevisiae May Contain Additional Medium-chain Fatty Acidmentioning
confidence: 72%
“…The latter is corroborated by the greater effect that sorbic acid has on the membrane potential, while acetic acid carries only bulk volume protons across the membrane until a steady state is reached, allowing ⌬ to remain relatively unaffected. Even though some authors have pointed to the similar effects of the uncoupler 2,4-dinitrophenol and sorbic acid on growth and metabolism (9,33,34), to our knowledge no quantitative measurements of the effect that sorbic acid has on ⌬ have been reported thus far. While relatively little research on the effects that WOA preservatives have on the membrane potential of microorganisms has been published (6,16,29,35,36), the depletion of ⌬ may have a plethora of effects.…”
Section: Discussionmentioning
confidence: 94%
“…A comparative study of inhibition by a weak acid (sorbic acid), an uncoupler (2,4-dinitrophenol) and a carboxylic acid (decanoic acid) observed that the carboxylic acid caused rapid cell death relative to the other two inhibitors and concluded that the mechanism of inhibition by carboxylic acids must be distinct from the other two molecule types (Stratford and Anslow, 1996). Desbois and Smith (2010) briefly review the association of molecule structure and shape with its potency as an inhibitor, but since most of these relationships deal with unsaturated molecules they are not discussed here.…”
Section: Characterization Of Inhibition As a Function Of Molecule Strmentioning
confidence: 99%